Peritoneal Protein Clearance Is Associated With Cardiovascular Events but Not Mortality in Peritoneal Dialysis Patients - Niu, Wei; Yang, Xiaoxiao; Yan, Hao; Yu, Zanzhe; Li, Zhenyuan; Lin, Xinghui; Gu, Leyi; Ni, Zhaohui; Fang, Wei (Frontiers in Medicine, 2022)
Introduction: Association of peritoneal protein clearance (Pcl) with outcomes in peritoneal dialysis (PD) patients is uncertain. Thus, we aimed to investigate its impact on cardiovascular events and all-cause mortality in PD patients and factors associated with Pcl. Methods: Prevalent PD patients from January 2014 to April 2015 in the center of Renji Hospital were enrolled. At the time of enrollment, serum and dialysate samples were collected to detect biochemical parameters and Angiopoietin-2-Tie2 system cytokines. Mass transfer area coefficient of creatinine (MTACcr) and Pcl were calculated. Patients were dichotomized into two groups by the median of Pcl level, and were followed up prospectively until the end of the study (October 1, 2018). Results: A total of 318 PD patients (51.2% men, mean age 56.7±14.3 yrs, median PD duration 31.5 (12.1-57.2) months) were enrolled. Among them, 25.7% were comorbided with diabetes and 28.6% had a history of cardiovascular disease (CVD). After being followed up for up to 43.9 (24.2 - 50.3) months, 63 had developed cardiovascular events, and 81 patients died. Among them, the high Pcl group had occurred 39 cardiovascular events and 51 deaths, and the low Pcl group had 24 cardiovascular events and 30 deaths. Kaplan-Meier analysis showed that, both cardiovascular events occurrence and all-cause mortality increased in patients with high Pcl. However, after adjusting for important confounders and serum Angiopoietin-2 level, Pcl was still an independent risk factor for cardiovascular events (HR, 95% CI, p) but not mortality (HR, 95% CI, p). On multivariate regression analysis, serum albumin, MTACcr, pulse pressure, BMI were found to be independently associated with Pcl. Conclusion: High Pcl is an independent risk factor for cardiovascular events but not all-cause mortality. The prediction of cardiovascular events by Pcl was independent of serum Angiopoietin-2.